The influence of social norms on the consumption pattern of Hausa-Fulani people in Nigeria - Haladu, Alhassan (Society of Scientific Research and Education (SSRE), 2016)
Customs and traditions have for long shaped the consumption patterns and habits of so many societies.Social values that range from historic, traditional, customary, religious, etc. have played a great role in what people eat, wear, and use generally.This work is an attempt to validate the assertion that social norms are not responsible for the consumption pattern of the Hausa-Fulani ethnic group of Nigeria. Using the Hausa-Fulani population in Kano State, a survey was carried out on 150 residents of each of the 44 local governments of the State. Kano State was chosen because it gives a fair reflection of the Hausa and Fulani spread in Nigeria and the West African sub-region.The data, analysed through OLS regression showed among other things that traditional and modern values have significant influence on Hausa-Fulani consumers.However, while traditional values have direct impact modern values have an inverse effect. Religion has no significant influence on their consumption pattern.This is mainly due to the high rate of poverty.Conclusively, though religious values are considered very highly in Hausa-Fulani societies; traditional and modern social values are what determined their consumption behavior.